Efficacy and tolerability of EH301 for amyotrophic lateral sclerosis: a randomized, double-blind, placebo-controlled human pilot study. Issue 1 (2nd January 2019) - de la Rubia, JosÉ E.; Drehmer, Eraci; Platero, JosÉ L.; Benlloch, MarÍa; Caplliure-Llopis, Jordi; Villaron-Casales, Carlos; de Bernardo, Nieves; AlarcÓn, Jorge; Fuente, Cristian; Carrera, Sandra; Sancho, David; GarcÍa-Pardo, Pilar; et al.
Abstract: Background : Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease, characterized by progressive loss of spinal and cortical motor neurons, leading to muscular atrophy, respiratory failure, and ultimately death. There is no known cure, and the clinical benefit of the two drugs approved to treat ALS remains unclear. Novel disease-modifying therapeutics that are able to modulate the disease course are desperately needed. Our objective was to evaluate the efficacy and tolerability of Elysium Health's candidate drug EH301 in people with ALS (PALS). Methods : This was a single-center, prospective, double-blind, randomized, placebo-controlled pilot study. Thirty-two PALS were recruited thanks to the collaboration of the Spanish Foundation for ALS Research (FUNDELA). Study participants were randomized to receive either EH301 or placebo and underwent evaluation for 4 months. Differences between EH301 and placebo-treated participants were evaluated based on standard clinical endpoints, including the revised ALS functional rating scale (ALSFRS-R), forced vital capacity (FVC), and the Medical Research Council (MRC) grading scale. Results : Compared to placebo, participants treated with EH301 demonstrated significant improvements in the ALSFRS-R score, pulmonary function, muscular strength, and in skeletal muscle/fat weight ratio. EH301 was shown to significantly slow the progression of ALS relative to placebo, and even showed improvements in several key outcome measures compared with baseline. Conclusions : This study provides evidence in support of the disease-modifying effects of EH301 for the treatment of ALS. Trial registration: ClinicalTrials.gov identifier: NCT03489200.